Study the Correlation between Chlamydial Infection and Some Novel Biomarkers in Fertile Women - Basma Salman (Journal of Global Pharma Technology, 2018)
Objective: The aim of present study was designed to detect of chlamydia trachomatis bacteria in infertile women, and its correlation with some novel biomarkers includes (AMH and MFG-E8).Methods: The current study include 60 infertile subjects with age range 15-45 years and 30 healthy control subjects, divided into four groups depending on diagnosis with chlamydia trachoma is IgG. Results: The present study had been shown a high significant differences between four groups were [P ˂ 0. 001] according to chlamydia trachomatis Ig-G infection and MFG-E8 marker. There are highly significant differences among percentage of AMH levels (high, low& normal), in fertile and infertile subjects. The present study showed no significant statistical difference were [p>0.05] among the effect of AMH on age, FSH, LH, PRL, Testo, and MFG-E8 in infertile patients. According to the results of present study that has been shown a highly significant difference [p ˂ 0.006 and 0.003, respectively] in FSH and prolactin levels between fertile and infertile patients, while the serum levels of LH, Testosterone and MFG-E8 show no significant differences [p˃0.05] in both fertile and infertile patients. Conclusion: The results of the present study showed a significant correlation between chlamydial infection andMFG-E8 marker while no significant correlation between chlamydial infection and AMH marker.Keywords: female infertility, chlamydia trachomatis, AMH, MFG-E8.